STATUS OF CERVICAL CANCER VACCINATION AMONG FEMALE HIGH SCHOOL STUDENTS AT CHU VAN AN PRIMARY, LOWER SECONDARY, AND UPPER SECONDARY SCHOOL, TO HIEU WARD, SON LA PROVINCE IN 2025 AND ASSOCIATED FACTORS (Vietnam Journal of Community Medicine, 2026)
Objective: Describe the current status of cervical cancer vaccination among female high school students at Chu Van An Primary, Secondary and High School in 2025 and some related factors.Research method: A cross-sectional descriptive study design was conducted on 108 female students from grades 10-12 at Chu Van An Primary, Secondary and High School in 2025, collected through a prepared questionnaire.Results: The rate of cervical cancer vaccination was 36.1%; of which the rate of full vaccination was 25.9%. The most common reason for vaccination was to prevent the disease (76.9%). The reason for not being vaccinated was fear of post-vaccination reactions (34.8%) and family economic conditions (30.4%). 23.2% did not know about the vaccine. In the future, 87% of the subjects were willing to get vaccinated. There is a correlation between the factor of having parents who are health workers and the status of cervical cancer vaccination (p
Keywords: female students, vaccine, cervical cancer.